Instilling Multicultural Values in the Sikep Samin Community in Klopoduwur Village, Blora, Central Java - Saputri, Retna Widya Umar; Arif, Dikdik Baehaqi (Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
This research is descriptive and qualitative to examine Sikep Samin multicultural principles. The subjects are the Sikep Samin figure, the Sikep Samin community and the community in Klopoduwur Village. Data is collected through interviews, observation, and documentation. The data analysis process includes reduction, presentation, and verification. This study found: 1) The Sikep Samin community in Klopoduwur Village promotes human values, honesty, politeness, and openness; 2) Habituation of behavior, traditional event meetings, and the Sangkan Paraning Dumadi community instill multicultural values; and 3) Internal constraints constrain multicultural values. External limitations are the stereotypes of ordinary people who are unfamiliar with foreign cultures, producing negative stereotypes in that civilization (The Sikep Samin community).